Effectiveness of Client-Centered Group Counselling in Enhancing Social Skills of Anxious Introverted Students - Indah Nurhaliza; Fauziah Nasution (Journal of General Education and Humanities, 2025)
This study examines the effectiveness of group counselling services employing the Client-Centred Therapy approach in enhancing the social skills of students with anxious introverted traits. Employing a quantitative method with a One-Group Pretest-Posttest Design, the study involved 11 seventh-grade students of MTs Al-Ulum Medan who were identified as having high levels of anxious introversion. The instrument used was an introversion scale, and the data were analysed using the Wilcoxon Signed-Rank Test. The findings revealed a significant decrease in introversion levels after the intervention, with all participants shifting from the high category (121–134; 76%–84%) to moderate and low categories (113–119; 71%–74%). Statistical analysis indicated Z = -2.950, p = 0.003 (< 0.05), and effect size r = 0.89, which reflects a significant effect. These results demonstrate that Client-Centred Group Counselling is effective in reducing social anxiety and enhancing students’ social skills, particularly in areas such as communication, cooperation, and self-confidence. The study highlights that school counsellors are encouraged to adopt client-centred group counselling as part of their structured psychosocial support. Further research is recommended to expand this model across various school contexts with larger samples, stronger experimental designs, and long-term evaluations.